BENTUK TARI KEMBANG KEMANGI KARYA JAJULAIDIK DAN YUDA GADIS OCTIANI SANGGAR TARI SAYUWIWIT - Anggraini, Maya Lestari; Slamet (Institut Seni Indonesia Surakarta, 2024)
This research describes the form and choreography of the Kembang Kemangi dance by Jajulaidik and Yuda Gadis Octiani from the Sayuwiwit Dance Studio. Kembang Kemangi dance is the new choreography inspired by the local tradition of Banyuwangi. The research questions include: (1) What is the form of the Kembang Kemangi dance by Jajulaidik and Yuda Gadis Octiani from the Sayuwiwit Dance Studio, (2) How is the choreography of the Kembang Kemangi dance by Jajulaidik and Yuda Gadis Octiani from the Sayuwiwit Dance Studio. In dissecting the formulation of the problem in this research, the theory of form and choreography by Slamet, in his book entitled